Pengembangan Labsheet Praktikum Uji Tekuk (Buckling) pada Mata Kuliah Fenomena Dasar Mesin Prodi S1 Pendidikan Teknik Mesin FT UNP - Putra, Romi; Sari, Delima Yanti; K, Arwizet; Wulansari, Rizky Ema (TSAQOFAH, 2025)
The buckling test labsheet used in the Fundamental Mechanical Phenomena course within the Undergraduate Program in Mechanical Engineering Education at the Faculty of Engineering, Universitas Negeri Padang (UNP), has been identified as having limitations in its instructional content. This study aims to develop and refine the labsheet to ensure adequate material coverage and a high level of feasibility for use in practical learning activities. The research employed a Research and Development (R&D) method using the Plomp development model, with a quantitative research design. Validation was conducted by three validators: the course instructor, a subject matter expert, and a media expert from the Department of Mechanical Engineering, FT UNP. Data were collected through a Likert-scale validation questionnaire and analyzed using quantitative descriptive techniques. Results from the material aspect showed that the subject matter expert gave an average score of 3.07 (76.75%), categorized as “Feasible,” while the course instructor provided a score of 3.23 (80.75%), categorized as “Highly Feasible.” For the media aspect, the media expert gave an average score of 3.59 (89.75%), and the course instructor provided a score of 3.43 (85.75%), both falling into the “Highly Feasible” category. Based on these findings, it can be concluded that the developed practical labsheet is categorized as “Highly Feasible” for use in practical sessions of the Fundamental Mechanical Phenomena course and holds potential as a reference for further research in the field of technical instructional material development.